2015
DOI: 10.1016/j.euromechflu.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The structural sensitivity of open shear flows calculated with a local stability analysis

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 30 publications
2
60
0
Order By: Relevance
“…To reduce the numerical effort, the stability problem (3) is first solved locally and the global stability properties are thereafter deduced from the local stability properties. The same approach has recently been adopted in several related studies dealing with swirling and non-swirling wake flows [34,36,[40][41][42]61,62]. A local eigenvalue problem is posed by adopting a quasi parallel, axially symmetric velocity profile…”
Section: Determining the Global Instabilitymentioning
confidence: 99%
“…To reduce the numerical effort, the stability problem (3) is first solved locally and the global stability properties are thereafter deduced from the local stability properties. The same approach has recently been adopted in several related studies dealing with swirling and non-swirling wake flows [34,36,[40][41][42]61,62]. A local eigenvalue problem is posed by adopting a quasi parallel, axially symmetric velocity profile…”
Section: Determining the Global Instabilitymentioning
confidence: 99%
“…A formal link between the two concepts was established in Juniper & Pier (2014). Here, we have shown that the global mode wavemaker of the Turbomeca flow lies inside the nozzle.…”
Section: Relation To Local Stability Analyses In Swirling Jets and Inmentioning
confidence: 99%
“…Figure 8(b) shows the structural sensitivity based on the local stability analysis where the global adjoint modes were reconstructed from the local analysis data according to Ref. [13]. Like in the global analysis, the region of highest structural sensitivity is located at the exit of the primary injector.…”
Section: Resultsmentioning
confidence: 99%
“…Adjoint methods based on global stability analysis give valuable insight into the internal feedback of hydrodynamic instability mechanisms. Juniper and Pier [13], for example, used structural sensitivity analysis to find the location of highest sensitivity to changes in the internal feedback mechanism of a confined co-flow wake and a cylinder wake, using both local and global stability analysis. Recently, Tammisola and Juniper [14] used global stability analysis on the mean flow in the interior of a fuel injector.…”
Section: Introductionmentioning
confidence: 99%